2020
DOI: 10.1101/2020.06.09.142760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hidden in plain sight: The effects of BCG vaccination in COVID-19 pandemic

Abstract: To investigate the relationship between BCG vaccination and SARS-CoV-2 by bioinformatic approach. Two datasets for Sars-CoV-2 infection group and BCG-vaccinated group were downloaded. Differentially Expressed Genes were identified.Gene ontology and pathways were functionally enriched, and networking was constructed in NetworkAnalyst. Lastly, correlation between post-BCG vaccination and COVID-19 transcriptome signatures were established. A total of 161 DEGs (113 upregulated DEGs and 48 downregulated genes) were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…26 The importance of vitamin D and immunity is echoed by the fact that Bacillus Calmette-Guérin (BCG) vaccination in COVID-19 patients appears to have a protective effect via the upregulation of the same pathways mentioned above. 24 Differences noted in subgroup analyses could be attributed to…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 The importance of vitamin D and immunity is echoed by the fact that Bacillus Calmette-Guérin (BCG) vaccination in COVID-19 patients appears to have a protective effect via the upregulation of the same pathways mentioned above. 24 Differences noted in subgroup analyses could be attributed to…”
Section: Discussionmentioning
confidence: 99%
“…Cathelicidins serve to disrupt the bacterial cell membranes, as well the enveloped viruses such as SARS‐CoV‐2, while defensins promote chemotaxis of inflammatory cells via increased capillary permeability 23 . Despite vitamin D promoting the expression of several inflammatory cytokines via T‐cell inactivation and interferon‐γ activation, 24 it simultaneously downregulates pro‐inflammatory markers interleukin‐6 and tumor necrosis factor‐α the two key cytokines involved with the development of the “cytokine storm” that precedes ARDS 25 . Given this understanding at the molecular level, one can reasonably imply that patients with vitamin D deficiency are at an increased risk of developing more severe manifestations of COVID‐19 and/or worse prognosis 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] In a molecular study, it was also shown that BCG vaccination is protective against SARS-CoV-2 by nonspecific ways. [8]…”
Section: Discussionmentioning
confidence: 99%
“…[3,6] Innate immune cells (monocytes, macrophages, natural killer cells) which are prepared by microbial PAMPs for a secondary exposure; play a role in trained immunity [3,7] and these cells increase the release of the proinflamatuarty cytokines (Interleukin-1β, tumor necrosis factor, and interleukin-6). [8]…”
Section: Introductionmentioning
confidence: 99%